Concrete Media to Increase Activities and Cognitive Learning Outcomes of Addition and Subtraction - Kastiniwati; Firman Ferdiansyah (Universal Education Jurnal Teaching and Learning, 2024)
In order to improve cognitive thinking skills and the student’s learning activities concerning mathematics, specifically on addition and subtraction topics, concrete media is employed in this research. The research was conducted as a Classroom Action Research (CAR) in the form of the Kemmis & McTaggart model and targeted at grade II students of SDN 184/V Parit Ponco, Jambi Province, with seven participants. The implementation of research is confined to the following four phases, i.e., planning and action, observation, and reflection, with a focus on the fact that some observation is done simultaneously with action. The application of such tools as colorful pictures, sticks, and real objects enabled the students to picture and physically interact with quite abstract objects in mathematics. This enhanced their interest and understanding of the subject matter. The results have shown improvement in learning outcomes and the level of student activity across cycles. The average score of cognitive outcomes, which was 32.86 in the pre-cycle, has improved to 45.71 in cycle I and 75.71 in cycle II. Similarly, students’ level of learning activity increased from 39.16% in pre-cycle to 75.23% in Cycle I and 87.39% in Cycle II. Concrete media, such as its interactive and practical aspects, worked well with different learning preferences in the classroom and served to call for active participation, teamwork, and self-directed problem-solving. This method also puts to practice the fact that linking theory to practice helps students to understand and remember better because it becomes clear and concrete and facilitates the notion that learning should be purposeful, cognitive, and contextualized for the student so that learning can be long-lasting and meaningful. From this research, it is evident that concrete media can help in improving elementary education and can be utilized in other learning environments.